A review on approaches and tools used in assessing indoor environmental quality - Gyimah, Kwabena Abrokwa; Abanyie, Samuel Amos; Koranteng, Christian (Penerbit Universiti Kebangsaan Malaysia, 2019)
The quality of an indoor space is very paramount as the well-being of occupants largely depends on it. Various standards have been developed to achieve quality indoor spaces. However knowledge of these standards does not guarantee quality indoor spaces. This review evaluates existing means of assessing indoor environmental quality ( IEQ) and proposes the appropriate for optimum results. 41 articles from highly ranked journals were conveniently sampled between the years 2007 to 2017. Review shows that even though more publications were done in 2012, indoor air quality had more publications done within the sampled years. Both subjective and objective assessments are used for IEQ assessments. Objective assessments are preferred over subjective assessments due to some limitations with subjective assessments. Subjective assessments should be better with validation from measured data. Various tools were identified for measured data collection but it is important to choice and instrument which is well calibrated and the data range it’s within the range of data to be taken. Software such as Ecotect, Design Builder, IES VE, Contam, Radiance, Energy Plus, Day Sim and TAS were identified as software for simulation purposes. However, since one software cannot be used to simulate all four variables (thermal, light, sound and air quality) of IEQ, a combination of Ecotect and Contam was proposed. The review concludes with the recommendation that both objective and subjective assessments should be used but always should be backed with validation